Non opioid rectal suppositories in post cesarean delivery pain management - a randomized trial - Murshed, Hasan; Haque, Mozibul; Islam, Rofiqul; Ferdousi, Mahmuda Ashrafi; Wahab, Md Abdul (Journal of Society of Anesthesiologists of Nepal, 2015)
Background: Frequent administration of intravenous or intramuscular analgesics is cumbersome in developing countries where skilled nursing staffs are at scarcity. We compared analgesic efficacy between regimen using rectal suppositories only (diclofenac and paracetamol) and regimen using conventional (fixed dose schedule) intramuscular pethidine in patients undergoing cesarean section. Methods: This prospective randomized single blind study included 144 patients undergoing both emergency and elective cesarean section. Suppositories group received diclofenac (50 mg) and paracetamol (1000 mg) suppositories regimen eight hourly for the first 24 hours. Pethidine group received intramuscular pethidine (75mg) eight hourly for the 24 hours. Effectiveness of analgesic regimen was inferred from visual pain score and satisfaction score. Results: Mean visual pain score in two groups was not statistically significant. But higher satisfaction score (Mean ±SD 6.36±1.306 vs 5.83±1.061; p<0.05) and less consumption of rescue analgesic (p < 0.001) was observed in suppositories group than pethidine group. No incidences of abnormal lochia /post-partum hemorrhage or other side effects were found in any study patient. Conclusions: The analgesic regimen using suppositories has not only enhanced patient satisfaction also reduced opioid consumption, thus reduced frequency of intramuscular injection in postoperative ward following cesarean sections. Journal of Society of Anesthesiologists of Nepal 2015; 2(2): 56-61